(untitled) (Biological Sciences - PJSIR, 1998)
The work has been carried out to evaluate the effects of studied pesticides on food constituents in cotton seeds and wheat grains. The results are assessed using analytical data from trial applications of organochlorine, organophos- phorus and synthetic pyrethroid pesticides to the aforesaid food commodities. The studied samples were stored after pesticide treatment at (30o±3"C) for one month and analyzed for carbohydrates, lipids, phosphorus and trace metals in triplicate alongwith control samples.The data presented herein shows adverse effectson carbohydrates in samples of cotton seeds and wheat grains with pesticidal treatment while SP pesticides caused more adverse effect than OC and OP·pesticides and reduced an appreciable amount of lipids in both commodities. It was also observed that phosphorus content decreased in cotton seeds and wheat grains treated with OC and SP pesticides but it increased in case of OP treatment. Lead (toxic element) was totally absent.